2022
DOI: 10.1200/cci.22.00032
|View full text |Cite
|
Sign up to set email alerts
|

MTPpilot: An Interactive Software for Visualization of Next-Generation Sequencing Results in Molecular Tumor Boards

Abstract: PURPOSE Comprehensive targeted next-generation sequencing (NGS) panels are routinely used in modern molecular cancer diagnostics. In molecular tumor boards, the detected genomic alterations are often discussed to decide the next treatment options for patients with cancer. With the increasing size and complexity of NGS panels, the discussion of these results becomes increasingly complex, especially if they are reported in a text-based form, as it is the standard in current molecular pathology. METHODS We have d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In the field of conventional tumour board software solutions, several studies have already shown that virtualisation can optimise patient management [49]. In their observational study investigating the structuring processes and the implementation of a virtual multidisciplinary tumour board, Blasi et al (2021) described how an efficient virtualisation and database system can potentially save time [50].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of conventional tumour board software solutions, several studies have already shown that virtualisation can optimise patient management [49]. In their observational study investigating the structuring processes and the implementation of a virtual multidisciplinary tumour board, Blasi et al (2021) described how an efficient virtualisation and database system can potentially save time [50].…”
Section: Discussionmentioning
confidence: 99%